MOTIVASI BERPRESTASI PEMAIN SEPAKBOLA JUNIOR SSB PERISAI KOTA PAYAKUMBUH - Masrun; Rifano Adiza; Yanuar Kiram; Roma Irawan (JURNAL ILMU KEOLAHRAGAAN, 2026)
This study aims to determine the relationship between achievement motivation and the performance of soccer players at SSB Perisai in Payakumbuh. This study employs a quantitative descriptive approach using a correlational method. The study population consisted of 35 players, with a sample of 20 selected using purposive sampling. The instrument used was a achievement motivation questionnaire with a Likert scale covering aspects of intrinsic and extrinsic motivation. Data analysis techniques included the Liliefors normality test and product-moment correlation analysis. The results indicate a significant relationship between achievement motivation and player performance, with a correlation coefficient of 0.781—greater than the critical value of 0.444 at a significance level of α = 0.05. This suggests that the higher a player’s achievement motivation, the better their performance. Thus, achievement motivation plays a crucial role in enhancing soccer players’ performance.